بلاغات الرواة في سنن أبي داود: جمع وتخريج ودراسة - مقاط، عبدالله عبدالمعطي صبحي (عبدالفتاح محمود إدريس, 2021)
هذه البحث بعنوان: «بلاغات الرواة في سنن أبي داود: جمع وتخريج ودراسة». ويهدف إلى جمع بلاغات الرواة من سنن أبي داود، ومن ثم تخريجها وتتبـع طرقها بما يساعد في دراستها وبيان أحوالها من حيث الاتصال والانقطاع، والقبول والرد. واعتمد الباحث المنهج الاستقرائي التام في جمع بلاغات الرواة من خلال كتـاب سنن أب داود، ومن ثم اجتهد في دراسـتها دراسـة علميـة، وذلـك بتقسـيم البلاغـات علـى فصول الدراسة ومباحثها، مع إبراز البلاغ، وإثبات نسبته إلى قائله، وتتبع طرقه؛ وبيان ما اتصل إسناده، وتخريج الأحاديث النبوية والآثار التي اشتملت على البلاغ من مصادرها الأصيلة، والحكم على أسانيدها، وبيان خلاصة القول في البلاغ، والوقوف على بعض الأحكام المترتبة عليه، مع التعريف بالأماكن والبلدان، وبمصطلحات علوم الحديث، وبيان الألفاظ الغريبة، وضبط الأسماء، والكلمات المشكلة عند الحاجة.
This study aims at collecting narrators’ Hadith reports from the books mentioned, and then checking its authenticity by following narrators’ methods in a way that helps in studying them and clarifying their status in terms of continuity of, interruptions in, acceptance or rejection of the chain of narrators., The researcher used the complete inductive approach to collect reports of narrators through the six Hadith books and Ahmad’s Musnad. The study, then, examines in a scientific manner such reports and distributing them on the chapters of the study and its subjects, highlighting reports, and referring them to their narrators, and following its tracks. The study then authenticates the Prophetic traditions and the effects such reports from its original sources, judging its chain of narration, and explaining the finale rules relevant to such reports. This is in addition to examining some of the rulings on it, with the definition of places and countries, the terms of hadith sciences, the showing the strange words, names, and vowelized words when needed.
Keywords: الأحاديث النبوية -- أسانيد الأحاديث -- رواة الأحاديث -- بلاغات الرواة -- كتب الحديث -- كتاب "سنن أبي داود"